Climate Change and Ocean Acidification: A Bibliometric Mapping of Scientific Literature - Judijanto, Loso (West Science Interdisciplinary Studies, 2025)
Climate change and ocean acidification represent two of the most pressing and interconnected environmental challenges of the 21st century, with profound implications for marine ecosystems and global sustainability. This study conducts a comprehensive bibliometric analysis of scientific literature at the intersection of these two domains to uncover trends, collaborations, and thematic developments from 2000 to 2024. Using data retrieved from the Scopus database and analyzed with VOSviewer, we mapped co-authorship networks, keyword co-occurrence, temporal evolution, and country-level collaborations. The results reveal a dynamic shift in research focus—from early chemical and geophysical mechanisms to more recent explorations of ecosystem-level impacts, biological metabolism, and interdisciplinary approaches. Leading contributors include authors such as Caldeira, Doney, and Kroeker, with dominant research hubs located in the United States, United Kingdom, and Netherlands. The analysis also highlights growing international collaboration and identifies underrepresented regions and emerging topics that warrant further attention. This study contributes to the theoretical understanding of knowledge structuring in environmental science and provides practical insights for shaping future research agendas, fostering global cooperation, and aligning scientific inquiry with policy and conservation priorities.